Assessment of physical and thermal behaviour of chitosan-based biocomposites reinforced with leaf and stem extract of Tectona grandis. (22nd February 2022) - Rahman, Lutfor; Goswami, Jutika; Choudhury, Devasish
Chitosan (Ch) has been incorporated with Tectona grandis leaf extract and stem extract at different compositions (5%, 10% and 15% v/v) to study the physicochemical properties of the biocomposites. The thin-film composites were prepared by the solution casting method to investigate the removal of chromium (VI) from water at varied pH conditions. The results showed that incorporation of the plant extracts improved the mechanical and UV barrier properties of the TFCs. Thermo-gravimetric analysis (TGA) showed that the degradation temperature of the films containing the extracts improved only slightly in comparison to the control film. Adsorption studies showed that for maximum Cr (VI) removal, Ch-L5 and Ch-L10 films were efficient. These eco-friendly prepared films are cost-effective and can also be a suitable material for food packaging.